Role of Theory in Public Administration Research - بن إسماعيل عياد (Dirasat in Economics and Business, 2020)
The general purpose of science is to expand knowledge through the discovery of facts. Theory in this regard can be seen as the main instrument by which researchers strive to achieve this purpose. Theory generally underpins research designs since it provides understanding of the phenomenon under investigateon. In this regard, theory functions as a mental model atempting to explain how aspects of social reality work. So the purpose of this paper is contributing towards improving the scientific rigour of research within Public Administration in general, and postgraduate studies in particular. This is done by clarifying the extent of the possibility of relying on theory in public administration to deal with various facts and events.